Low‐depth sequencing for copy number abnormalities in multiple myeloma supersedes fluorescent in situ hybridization in scope and resolution. Issue 2 (29th May 2019) - Elnenaei, Manal O.; Knopf, Philipp; Cutler, Samuel D.; Sinclair, Keaton; Abou El Hassan, Mohamed; Greer, Wenda; Goudie, Marissa; Wagner, Julie; White, Darrell; Couban, Stephen; Forward, Nicholas; Gaston, Daniel; et al.
Abstract: Multiple myeloma (MM) is an incurable hematological malignancy that relies on cytogenetic determination of copy number abnormalities (CNAs) for prognosis and management. Low‐depth whole genome sequencing (LD‐WGS) is a cost‐effective alternative to targeted genomics for CNA detection, but its value has yet to be explored in MM. DNA from CD138+ cells from MM patients were sequenced using an Illumina NextSeq at <1x depth (ultralow‐depth). Subsampling analysis and window size adjustment were performed for determining sensitivity limits and results compared to fluorescent in‐Situ hybridization (FISH). CNA calls made down to 5 million (M) reads were comparable to those at 20 M reads at a window size of 100 kb had a sensitivity and specificity of 93%, 92% and an area under the curve of 0.94. All CNAs detected by FISH on the MM samples were also detected by LD‐WGS; the latter detected a further 36 focal CNAs not detected by FISH. Cost per sample of LD‐WGS was significantly lower for our organization than FISH testing. LD‐WGS for MM is significantly more sensitive than targeted technologies such as FISH in CNA detection and resolution, provides a more cost‐effective option for clinical purposes and potential for exploring prognostically relevant and drug discovery targets. Abstract : Overview of individual copy number abnormalities on each chromosome arm as detected by LD‐WGS. F: Copy number abnormality also detected by FISH. *Two non‐overlapping deletions detected by LD‐WGS on 17p.